Percutaneous Transvenous Removal of an Entire Detached Port Catheter by Using a Snare-Loop Catheter in a 13-Month-Old Child (Annals of Medical Research, 2021)
None
Keywords: Port Catheter; Percutaneous Retrieval; Child; Snare-Loop Catheter.